Glacioeustasy during the middle Eocene? Insights from the stratigraphy of the Hampshire Basin, UK - Dawber, C; Tripati, A; Gale, A; MacNiocaill, C; Hesselbo, S (2011)
The sedimentary strata of the Hampshire Basin constitute some of the best-preserved Palaeogene sequences worldwide, and include the traditional 'unit stratotype' for the Bartonian (~. 36.9-41.4. Ma). The Barton Clay Formation at Alum Bay on the Isle of Wight (IOW) was studied to assess the evidence for middle Eocene sea-level variation in records of grain size, sediment properties, faunal assemblage, foraminiferal diversity indices and foraminiferal stable isotopes. Sedimentary cycles of 1-10. Myr (third order) and 0.2-0.5. Myr (fourth order) duration are reported and interpreted to reflect ~. 20-60 metre variations in water depth. Additionally, an integrated magneto-bio-chemostratigraphical age model for the succession at Alum Bay is presented and new and published litho- and bio-stratigraphical markers are used to correlate additional successions. Based on this age model, it appears that during the late Lutetian and early Bartonian (~. 42-38. Ma), water depth variation identified within the basin was synchronous. Sedimentary and fossil evidence supports episodic uplift in the eastern part of the Hampshire Basin during the Bartonian, which at present precludes the calculation of eustatic sea-level. However, the amplitude and frequency of water-depth variations identified in the Barton Clay Formation, and correlations to published sea-level curves, are consistent with a component of these changes being glacioeustatic during the middle Eocene. There is also evidence for a large excursion (Δ18O>‰) in the mono-specific benthic foraminiferal oxygen-isotope record (Alum Bay) ~39.9Ma, which is correlated to the isotope excursion at the 'middle Eocene climatic optimum' previously reported in the Southern Ocean, and other localities. A contemporaneous water-depth increase of ~40m at Alum Bay may indicate that a component of this 'global' oxygen-isotope excursion results from a reduction in continental ice storage. © 2011 Elsevier B.V.